RISK AND RISK-TAKING IN SMALL BUSINESS ACTIVITIES - O‘ktamjonova , Zulayho; Yuldashev , Muzaffarbek Jakbaraliyevich; Abdumutalov , Otabek Rozmatjonovich (Educational Research in Universal Sciences, 2023)
In this article, small business operations usually have small financial resources compared to large corporations, and such businesses are subject to constant changes in security, economic viability, and other typical risks. A business owner should try to reduce risk, but only through their own personal trading strategies and organizational risk. This is very important in paying off debts and developing new businesses. Also, a business owner can take risks to grow and improve, while also taking risks in compliance, to win. In such a case, it is important for the business owner to understand and learn against future risks and deadlines, and to be prepared to address any issues in depth.